The degree of JIT in mineral oil and asphalt industries in Libya - Mohamed Elbishti, Entsar Kouni Alhaj (2015)
The focus of this research is to show the degree of the Just-in-time system implementation in mineral oil and asphalt manufacturing industries in Libya and to evaluate the availability of its elements, which are management support, human, inventory management, total quality management and their relationship with the cost and competitiveness. Also, to know the challenges those are faced in this system implementation. A 650 questionnaire was developed for the workers in the mineral oil and asphalt manufacturing industries in Libya and tested using the collected data that was gained from the sample. The interview was made with 16 managers and responsible people in the area to discuss the possibility level of the JIT implementation and the problems that may prevent the implementation. T- Test and F- test used through a simple linear regression and multiple regressions to identify the best model for the research variables. The findings strongly supported the hypotheses that the four main elements are available. The simple linear regression showed that all elements have a significant relationship with costs and only three have a relationship with a competitive position. The findings of this research showed that the lack of the awareness about the importance of JIT in the target factories is the limitation of this research. Also, the finding showed that the overseas suppliers, the lack of management support are the most challenges that prevent JIT implementation. Finally, the recommendations were made according to the findings, which were the importance of introducing the JIT and its advantages to the oil industries in Libya and trying to overcome the obstacles that may prevent its implementation. This research emphasizes that the success of this system depends on both humans and technology, therefore, four elements are suggested as the most important elements to succeed with the JIT implementation in the long term strategy implementation.